Transformasi Layanan Administrasi Kependudukan oleh Disdukcapil Kabupaten Bekasi di Masa Pandemi Covid-19 - Nuraini, Anggi (Jurnal Ilmu Administrasi Negara (JUAN), 2021)
This study aims to look at the quality of service in the process of transforming administrative services from an offline system to an online system provided by the Department of Population and Civil Registration of Bekasi Regency during the Covid-19 pandemic. This study was analyzed based on the Theory of Application of E-Government as a result of studies and research from the Harvard JFK School of Government which has the dimensions of Support, Cappacity and Value. The method used in this research is descriptive-qualitative. This paper has succeeded in finding that the Department of Population and Civil Registration of Bekasi Regency has been able to improve the quality of services in the midst of the Covid-19 pandemic which limits the activities of the community, including the processing of administrative documents by providing online services. However, in the process of transforming the online service system, it still has some shortcomings in terms of the facilities provided.